2021
DOI: 10.1515/jbcpp-2020-0178
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical sleep deprivation induces oxidative stress in the submandibular glands of Wistar rats

Abstract: Objectives Paradoxical sleep deprivation has been associated with impaired salivary secretion in rats. However, the mechanism that underlies this is not known. Therefore, this study assessed salivary and serum oxidative stress levels following paradoxical sleep deprivation in rats. Methods Twenty-one male Wistar rats randomly divided into three groups of seven rats each as; Control (C); partial sleep-deprived (PSD); and total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…MDA is a product of lipid peroxidation of polyunsaturated fatty acids by ROS, which reacts with various molecules (e.g., proteins, nucleosides, DNA, etc.) and may produce many adducts that promote cellular damage, and even lead to DNA mutation and induction of apoptosis (Lasisi et al., 2021 ). SOD is a key antioxidant enzyme that scavenges excess ROS and MDA, and its activity indirectly reflects the ability to scavenge oxygen radicals, and its reduced activity indicates antioxidant barrier damage.…”
Section: Resultsmentioning
confidence: 99%
“…MDA is a product of lipid peroxidation of polyunsaturated fatty acids by ROS, which reacts with various molecules (e.g., proteins, nucleosides, DNA, etc.) and may produce many adducts that promote cellular damage, and even lead to DNA mutation and induction of apoptosis (Lasisi et al., 2021 ). SOD is a key antioxidant enzyme that scavenges excess ROS and MDA, and its activity indirectly reflects the ability to scavenge oxygen radicals, and its reduced activity indicates antioxidant barrier damage.…”
Section: Resultsmentioning
confidence: 99%
“…As previously observed [ 9 ], the evidence from the included studies seems to point to changes in oxidative stress parameters in both brain (whole brain, hippocampus, cortex, thalamus, hypothalamus, amygdala, locus coeruleus) and non-brain areas (serum, testes, epididymis, liver, pancreas, aorta, submandibular glands, thyroid, erythrocytes, soleus muscle). However, some body sites did not show changes in oxidative stress parameters: cerebellum and brainstem [ 26 ], saliva [ 66 ], kidney [ 45 ], and plantar muscle [ 37 ]. While the evidence is limited in some cases, these observations might suggest that the antioxidant effects of sleep extend beyond the central nervous system, possibly including most body sites.…”
Section: Discussionmentioning
confidence: 99%
“…[85] also found that intestinal inflammation was triggered by an increase in proinflammatory cytokine levels in mice with sleep deprivation and that there was a decrease in gene expressions effective in the connections between the brain and the intestine, and as a result of these effects, intestinal permeability decreased. It has been found that the oxidative stress resulting from the disruption of oxidant/antioxidant balance in rats with paradoxical sleep deprivation leads to salivary secretion disorders [86]. According to Shigiyama et al [87], mice subjected to a 6-hour sleep deficiency period may develop hepatic steatosis and hepatic insulin resistance, with an increase in the levels of hepatic lipogenic enzymes perhaps acting as the underlying mechanism.…”
Section: Sleep Deprivation and The Gastrointestinal Systemmentioning
confidence: 99%